Reducing sitting time in office workers: Short-term efficacy of a multicomponent intervention - Healy, Genevieve; Eakin, E.; LaMontagne, A.; Owen, N.; Winkler, E.; Wiesner, G.; Gunning, L.; Neuhaus, M.; Lawler, S.; Fjeldsoe, B.; Dunstan, D. (2013)
Objective: To investigate the short-term efficacy of a multicomponent intervention to reduce office workers' sitting time. Methods: Allocation for this non-randomized controlled trial (n =43 participants; 56% women; 26-62. years; Melbourne, Australia) was by office floor, with data collected during July-September 2011. The 4-week intervention emphasized three key messages: "Stand Up, Sit Less, Move More" and comprised organizational, environmental, and individual elements. Changes in minutes/day at the workplace spent sitting (primary outcome), in prolonged sitting (sitting time accumulated in bouts =. 30. min), standing, and moving were objectively measured (activPAL3). Results: Relative to the controls, the intervention group significantly reduced workplace sitting time (mean change [95%CI]: - 125 [- 161, - 89] min/8-h workday), with changes primarily driven by a reduction in prolonged sitting time (- 73 [- 108, - 40] min/8-h workday). Workplace sitting was almost exclusively replaced by standing (+. 127 [+. 92, +. 162] min/8-h workday) with non-significant changes to stepping time (- 2 [- 7, +. 4] min/8-h workday) and number of steps (- 70 [- 350, 210]). Conclusions: This multicomponent workplace intervention demonstrated that substantial reductions in sitting time are achievable in an office setting. Larger studies with longer timeframes are needed to assess sustainability of these changes, as well as their potential longer-term impacts on health and work-related outcomes.